Ga-Supported MFI Zeolites Synthesized Using Carbon Nanotubes Containing Gallium Oxide Nanoparticles on Exterior Walls and in Interior Channels as Hard Templates for Methanol Aromatization - Chang, Ching Jung; Chen, Chin Han; Lee, Jyh Fu; Sooknoi, Tawan; Lin, Yu Chuan (My University, 2020)
A combinative approach of steam-assisted crystallization and hard templating was employed to prepare mesostructured Ga/ZSM-5 catalysts. Carbon nanotubes (CNTs) containing gallium oxide nanoparticles supported on the exterior surface and confined in the inner space were used as the templates. A comparative study showed that by using these two templates, the crystallinities, mesoporosities, and Ga coordination environments of mesostructured Ga/ZSM-5 catalysts were similar. However, a greater strength of Lewis acid of Ga/ZSM-5 was obtained using the GaOx-encapsulated CNTs as the template. Encapsulated GaOx was less reducible than those supported on the exterior surface of the CNTs, resulting in an increased concentration of isolated (GaO)+. Moreover, compared to pristine ZSM-5, the concentration of Brønsted acid was nearly intact by using GaOx-encapsulated CNTs as the templates. A better methanol aromatization performance was achieved by the Ga/ZSM-5 made by using GaOx-encapsulated CNTs.